Catchment Dissolved Organic Carbon Transport: A Modeling Approach Combining Water Travel Times and Reactivity Continuum. Issue 7 (22nd July 2022) - Grandi, G.; Bertuzzo, E.
Abstract: Quantifying the transfer of organic carbon from the terrestrial to the riverine ecosystems is of crucial importance to fully appreciate the carbon cycle at the catchment, regional and global scales. In this study, we propose a framework for modeling the flux of dissolved organic carbon (DOC) from hillslopes to stream and river networks which couples a transport model based on travel time distributions with the reactivity continuum (RC) approach to model DOC degradation. We test the model by applying it to the Plynlimon catchments (UK) exploiting both weekly and high‐frequency (7‐hr interval) time‐series. We use information about chloride to get an independent estimate of water travel times using the framework of StorAge Selection functions. Following the RC model, the composition and the degradation of DOC along the flowpaths, and its consequent concentration in the streamflow, is described assuming that DOC is composed by a mixture of compounds that follows a continuous spectrum of reactivity. For the high‐frequency data set, the model is able to reproduce DOC streamflow concentrations and to capture the complex hysteretic relation between DOC concentration and discharge. Weekly data are instead not frequent enough to properly describe DOC dynamics in this catchment. The distribution of the age of the water comprised in the streamflow proves thus a key variable to predict the quantity and the reactivity of the DOC exported from soils, and the effect of hydrologic variability on this process. Plain Language Summary: Streams and rivers are able to drain, transport, process and mineralize the carbon stored in the terrestrial ecosystems. This set of processes controls stream water quality, the metabolic functioning of riverine ecosystems, and eventually the carbon balance and the CO2 emissions at the global scale. We focus on the flux of dissolved organic carbon (DOC) originating from the decomposition of soil organic matter and exported from hillslopes to the streamflow by rainfall‐runoff processes. Our goal is to contribute to the understanding of this process and to disentangle the complex relation between DOC concentration and discharge. We estimate the quantity of DOC that survives the pathways from the soil to the stream using two key variables: the time that the water transporting DOC spends along the pathway and the DOC reactivity, which controls its degradation. The model is able to capture the complex behavior of stream DOC concentration in two headwater catchments, suggesting that the mixture of water with different ages that characterizes the streamflow controls the time available for degradation and thus the flux of DOC exported. Key Points: Quantity and reactivity of dissolved organic carbon (DOC) exported from a hillslope are modeled coupling water age and reactivity continuum The age structure of water in the catchment controls DOC degradation within soils DOC concentration‐discharge relations are explained by water travel time distribution